Paul's Argument in Romans 9–11 - Cook, Michael J. (Review and expositor, 2006)
Paul's poignant concern for the Jews, expressed in Romans 9–11, raises intriguing questions. The foremost is why it is only in Romans that Paul attends to relations between Jews and Christians (both Jewish- and Gentile-). While Paul styles himself the “apostle to the Gentiles,” in these three chapters he seems preoccupied with the Jews‘ destiny, insisting that only the infusion of Christian ranks by Gentiles will induce all Jews also, eventually, to come to Christ. Thereby, Paul radiates the odd impression that his apostleship to Gentiles is ultimately for Israel's sake, perhaps rendering Paul not only an apostle to the Jews after all but even the apostle par excellence. Indeed, so invested is he here in God's plan for the Jews that we must also ponder whether Paul sees his religious reorientation as an extension of his own Judaism rather than a departure from it. Given his zealous temperament, we may well wonder whether Paul had ever functioned as a missionary for Judaism, and whether, in effect, he is still doing so—except now for a Judaism that he has reconfigured. Why, instead of being touched by Paul's evident anxiety for Israel, do most modern Jews still recoil from him (perhaps echoing their counterparts from his own day)? Is the problem that what Jews hear today is less what Paul says than the way later Christianity reformulated it—in a more anti-Jewish direction? We see, in Romans 9–11, how urgently Paul warns Gentiles away from anti-Judaism, but might he do so precisely because he intuits how very compatibly his own thought could be processed directly in line with it? Does Paul himself furnish the theoretical structure for later Christian antisemitism?